Oxybarotherapy of uterine infertility - Ewa Zieliński; Piotr Dzięgielewski; Katarzyna Sas; Romuald Olszański; Walery Zukow (Kazimierz Wielki University, 2018)
The problem of oxybarotherapy of uterine infertility was proposed as a proposition of a safe complementary method of fertility improvement. The possibilities of using hyperbaric therapy and new directions of its application have been presented. Indications of hyperbaric therapy are constantly modified and new fields of its applications are noticed. A project for the use of aerobic hyperbole in the world was described and the possibility of implementing therapy to Poland was indicated. The benefits of supplementary therapy, which is oksybaroterapy in the treatment of couples with impaired uterine fertility, are presented.